2012
DOI: 10.1037/a0027119
|View full text |Cite
|
Sign up to set email alerts
|

The overview of reviews: Unique challenges and opportunities when research syntheses are the principal elements of new integrative scholarship.

Abstract: In the past two decades, a new form of scholarship has appeared in which researchers present an overview of previously conducted research syntheses on the same topic. In these efforts, research syntheses are the principal units of evidence. Overviews of reviews introduce unique problems that require unique solutions. This article describes what methods overviewers have developed or have adopted from other forms of scholarship. These methods concern how to (a) define the broader problem space of an overview, (b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
252
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 167 publications
(255 citation statements)
references
References 43 publications
0
252
0
3
Order By: Relevance
“…Also referred to in the literature as overviews of reviews, reviews of reviews, and systematic reviews of systematic reviews, umbrella reviews have the primary objective of addressing specific research questions by examination of the findings of previous reviews (Becker & Oxman, 2008). By synthesizing across previous reviews, patterns in findings can be identified that permit conclusions to be drawn about the state of research in an area, that help resolve discrepancies in conclusions drawn by different reviews, and can identify the direction future research should take (Becker & Oxman, 2008;Cooper & Koenka, 2012).…”
Section: Wjnr Welcomes Umbrella Reviewsmentioning
confidence: 99%
See 4 more Smart Citations
“…Also referred to in the literature as overviews of reviews, reviews of reviews, and systematic reviews of systematic reviews, umbrella reviews have the primary objective of addressing specific research questions by examination of the findings of previous reviews (Becker & Oxman, 2008). By synthesizing across previous reviews, patterns in findings can be identified that permit conclusions to be drawn about the state of research in an area, that help resolve discrepancies in conclusions drawn by different reviews, and can identify the direction future research should take (Becker & Oxman, 2008;Cooper & Koenka, 2012).…”
Section: Wjnr Welcomes Umbrella Reviewsmentioning
confidence: 99%
“…The validity and strength of conclusions drawn by any review article are dependent on the methodological quality of the review (Cooper & Koenka, 2012;Smith et al, 2011). Umbrella reviews should therefore always include a quality assessment of all included reviews.…”
Section: Wjnr Welcomes Umbrella Reviewsmentioning
confidence: 99%
See 3 more Smart Citations